2018
DOI: 10.3390/ijms19030801
|View full text |Cite
|
Sign up to set email alerts
|

cGMP Signaling in the Cardiovascular System—The Role of Compartmentation and Its Live Cell Imaging

Abstract: The ubiquitous second messenger 3′,5′-cyclic guanosine monophosphate (cGMP) regulates multiple physiologic processes in the cardiovascular system. Its intracellular effects are mediated by stringently controlled subcellular microdomains. In this review, we will illustrate the current techniques available for real-time cGMP measurements with a specific focus on live cell imaging methods. We will also discuss currently accepted and emerging mechanisms of cGMP compartmentation in the cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 125 publications
(176 reference statements)
1
10
0
1
Order By: Relevance
“…It has been previously reported that specificity of PKG signaling in cardiomyocytes is maintained via the involvement of pGC versus sGC (14). Consistent with this notion, our study demonstrated separate patterns of RyR2 PKG phosphorylation via ANPR and M2R, globally versus locally, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been previously reported that specificity of PKG signaling in cardiomyocytes is maintained via the involvement of pGC versus sGC (14). Consistent with this notion, our study demonstrated separate patterns of RyR2 PKG phosphorylation via ANPR and M2R, globally versus locally, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…It has been previously reported that specificity of PKG signaling in cardiomyocytes is maintained via the involvement of receptormediated particulate guanylate cyclase (pGC) and soluble guanylate cyclase (sGC) (13). In addition, there is evidence of cyclic guanylate monophosphate (cGMP) compartmentalization in cardiomyocytes whereby b3AR-eNOS-NO-sGC-NO-PKG(b 3 -adrenergicreceptor-endothelialnitricoxidesynthasenitric oxide-sGC-cGMP-PKG) signaling occurs separately from a pGC-cGMP pool mediated via atrial natriuretic peptide receptor (ANPR)-pGC-cGMP-PKG signaling (14). Although extensively characterized in other cell types (15,16), the specific molecular events linking muscarinic stimulation and cGMP-PKG-dependent phosphorylation of target effectors, including components of Ca handling, remain to be elucidated in cardiomyocytes.…”
mentioning
confidence: 99%
“…cGi500 has an EC 50 for cGMP of 500 µM (Russwurm et al, 2007), which is probably not optimized to detection of cGMP concentrations induced by neurohormonal stimuli. Another cGMP biosensor, redcGES-DE5, has an EC 50 of ∼40 nM (Nikolaev et al, 2006; Bork and Nikolaev, 2018) and could be used to detect small changes in cGMP concentration that are often present in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…[88]. Имеющиеся данные свидетельствуют о том, что молекулы цГМФ, образующиеся при стимуляции рГЦ и мГЦ, разобщены в пространстве внутри клеток, вследствие чего имеют отличающиеся функции, несмот ря на структурную идентичность [24,89]. Более того, при СН имеются риски развития резистентности миокарда и сосудов к BNP за счет снижения активности самих молекул или их рецепторов на клеточном уровне, а также инактивации при воздействии клеточных протеиназ [90].…”
Section: натрийуретические пептиды и неприлизинunclassified